2020
DOI: 10.1080/14616696.2020.1824004
|View full text |Cite
|
Sign up to set email alerts
|

Education, health behavior, and working conditions during the pandemic: evidence from a German sample

Abstract: Education is a main cause of health inequality because it influences health behavior as well as structural conditions that impact health, such as living and working conditions. We examine how different educational groups reacted to the beginning of the COVID-19 pandemic in Germany by looking at health-related behaviorsocial distancing, increased hygiene, and mask wearingas well as changes in working conditionswork from home, reduced working hours, and not workingas a structural indicator that can mitigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
2
22
0
1
Order By: Relevance
“…Other studies revealed a high use of protective behavior [7] and a rather low level of leisure time sport activities [8] during the pandemic. A certain number of studies concluded that the societal conditions surrounding COVID-19 increase gender, social, and educational inequalities [9,10]. All of these findings are in line with reviews about psychosocial impacts of quarantine measures during previous pandemics that consistently showed negative effects on mental health outcomes [11].…”
Section: Introductionsupporting
confidence: 63%
“…Other studies revealed a high use of protective behavior [7] and a rather low level of leisure time sport activities [8] during the pandemic. A certain number of studies concluded that the societal conditions surrounding COVID-19 increase gender, social, and educational inequalities [9,10]. All of these findings are in line with reviews about psychosocial impacts of quarantine measures during previous pandemics that consistently showed negative effects on mental health outcomes [11].…”
Section: Introductionsupporting
confidence: 63%
“…While this seems fine to get a first thorough impression, we should (and authors did) nevertheless treat findings based on such data with some caution. Future research could make use of existing panels and start collecting more representative data, which can also allow for replication and thus support more robust conclusions (Hoenig and Wenz 2020;Möhring et al 2020). In turn, some of the qualitative (small-N) studies were confronted with difficulties in terms of gaining access to particular social groups, particularly while social distancing measures were in place.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to educational inequalities, the papers in this special issue showed that there are social inequalities in home schooling efforts for high school students in Germany (Dietrich et al 2020). Moreover, education was found to be a strong predictor of COVID-19 related health behaviorphysical and social distancing, increased hygiene, and face mask wearingat least in Germany (Hoenig and Wenz 2020). Learning during the pandemic became a particular challenge for migrant children.…”
Section: Educational Inequalitiesmentioning
confidence: 99%
“…Chung and van der Lippe 2018), more than a quarter of the working population worked at least partly from home in spring 2020 (e.g. Hoenig and Wenz 2020;Schröder et al 2020). On the one hand, working from home might come with the potential benefit of spending more time with the partner and the family and is discussed as a measure to reconcile family and work (e.g.…”
Section: Introductionmentioning
confidence: 99%